Development of Quality and Integrity Islamic Higher Education in North Sumatra in KOPERTAIS IX - Ahmad Ibrahim Hasibuan; Hasan Asari; Neliwati Neliwati (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The purpose of this study is to describe and analyze the management of private Islamic tertiary institutions which are required to become quality tertiary institutions in terms of the accreditation obtained by the tertiary institutions themselves. The research method uses phenomenological qualitative. Primary data source; university leaders namely STIT Al-Hikmah Tebing Tinggi, IAIDU Kisaran, STAI Al Ihlas Sidikalang, FAI UISU, STAI Lubuk Pakam, and STAI Lubuk Pakam. Secondary data sources; research journals, books, and websites. Qualitative research data collection techniques, namely documentation, observation, and interviews. Descriptive-qualitative analysis techniques and reflective analysis. The research results of KERJASAMA IX North Sumatra have the task of supervising, controlling, fostering, and empowering private Islamic tertiary institutions. Provide consideration and follow-up sanctions against PTAIS that provide non/low quality education. Strategic steps that can be considered in the development of PTAI in the face of globalization are changing the Mindset from the Paradigm of Spectators to Actors, giving birth to graduates with an entrepreneurial spirit, Diplomacy of International Standard Academic Tracks, Sending Lecturers Abroad to Ministry of Religion Launching of 5000 Doctoral scholarship programs, Increasing Foreign Language Competence and global-based standardization of Academic Facilities.